Development of an ISP Partnership Business Model Using Business Model Canvas, SWOT, and AHP - Deni Kurniawan; Rahma Wahdiniwaty; Rano Khamidovna Nosirova (International Journal of Research and Applied Technology (INJURATECH), 2026)
The growth of the internet service provider industry has intensified competition in partnership-based business, necessitating the use of more structured and organized business partnership strategies. Although previous studies have combined the Business Model Canvas (BMC), SWOT analysis, and the Analytical Hierarchy Process (AHP), only a few have applied the concept of an internet service provider partnership business. This study aims to design a partnership business model for an internet service provider company by integrating the BMC, SWOT, and AHP methods. The mixed method that will be used in the study involves interviewing, observation, company documentations, and comparison questionnaires. The role of the Business Model Canvas (BMC) is to aid in analysis of the current business model, SWOT will be utilized in order to create strategic alternatives, and AHP will be used to rank the alternatives. From the research, the two main areas which need attention are increasing the ISP Network by developing new marketing/community partnerships (SO1), and enhancing the service improvement using integrated digital services (SO2). The two areas will be developed further into a Business Model Canvas. In this research, a framework of decision making that integrates BMC, SWOT analysis, and AHP is suggested to effectively transform the organization’s strategy into a BMC for ISPs. This framework could be used theoretically as a reference for integrating the strategy and business modelling and practically for designing the collaborative business model